(untitled) (Revista de Ciências Agroveterinárias, 2022)
This study aims to investigate the effect of different periods of fasting and re-feeding on compensatory responses in Nile tilapia fingerlings and the frequency of muscle fiber distribution. A total of 108 Nile tilapia fingerlings with initial weight of 1.64 ± 0.41 g and mean initial length of 3.60 ± 0.39 cm were used for 55 days. The fish were distributed in a water recirculation system in a completely randomized design with three treatments and four replications: Control - CO - (fish fed until apparent satiation throughout the experimental period); fasting 10 - J10 - (fish fed to apparent satiation for 15 days, followed by 10 days of fasting and re-feeding to satiation for 30 days); and fasting 15 - J15 - (fish fed to apparent satiation for 15 days, followed by 15 days of fasting and re-feeding to satiation for 25 days). Fish from the J15 treatment showed unsatisfactory results in terms of productive performance (p<0.05), such as lower final weight, apparent feed conversion, protein efficiency ratio, and survival, while fish from the J10 treatment achieved the same results as those animals kept in the CO treatment with the exception of the variables of relative weight gain and feed intake. Furthermore, food restriction directly influenced the growth of muscle fibers with a diameter smaller than 20 μm (p<0.05), and fish from the J15 treatment had the lowest frequency of fibers in this diameter class. Therefore, this study concludes that food restriction in short periods (10 days) and at low temperatures can present a compensatory growth, as they alter the process of hyperplasia and hypertrophy of muscle fibers without affecting the morphology of the fibers; however, 15 days of fasting under low temperatures do not compensate for growth and delays the hypertrophic growth of muscle fibers.